LA POESÍA DE JUDY GRAHN Y MARLENE NOURBESE PHILIP: CUESTIONES DE IDENTIDAD Y PRÁCTICAS DE TRADUCCIÓN GENERATIVA (Ágora UNLaR, 2019)
En “Generative Translation in Spicer, Gelman and Hawkey”, Lisa Bradford (2013) explica que los traductoresintentan “transplantar un texto a un nuevo paisaje lingüístico de manera exitosa” y que pueden lograrlomediante un estilo de traducción generativa, una poética que funciona para revelar y reavivar la articulaciónoriginal y producir, al mismo tiempo, un nuevo texto (p.2). A partir de una lectura comparativa de “Slowly: aplainsong from an older woman to a younger woman”, de Judy Grahn, y “Meditations on the Declension ofBeauty by the Girl with the Flying Cheek-bones”, de Marlene Nourbese Philip, este estudio plantea lasproblemáticas que surgen de la traducción de estos textos al castellano. Grahn, poeta estadounidense, esconocida por sus producciones de tinte política y sus contribuciones al movimiento lesbiano-feminista. Philip,poeta caribeña, describe en sus poemas las experiencias de la mujer negra y las cuestiones de pertenenciay lenguaje que derivan de la etapa colonial y postcolonial. Los textos seleccionados son, sin duda, clarasexposiciones de la ideología y posición de estas poetas y tratan la cuestión de la identidad mediante un juegointeresante de sonidos y repeticiones, la fragmentación, la dilación y el juego de palabras. Dadas estascaracterísticas, un tipo de traducción generativa que permita producir conversaciones con los textos originalesy generar nuevas imágenes se transforma en una opción interesante. THE POETRY OF JUDY GRAHN AND MARLENE NOURBESE PHILIP:ISSUES OF IDENTITY AND PRACTICES OF GENERATIVE TRANSLATIONAbstractIn “Generative Translation in Spicer, Gelman and Hawkey”, Lisa Bradford (2013) explains that translators tryto “successfully transplant a work into a new language-land in order to share and perpetuate its beauty”,however, not all of them “strive to clone the source text, preferring rather to cultivate it by means of generativetranslation”, a “translational poetics that functions to reveal and revive the original articulation while producingan entirely fresh work of art” (p.2).The comparative reading of “Slowly: a plainsong from an older woman to ayounger woman”, by Judy Grahn, and “Meditations on the Declension of Beauty by the Girl with the FlyingCheek-bones”, by Marlene Nourbese Philip, allows analyzing some of the issues that become evident whenattempting different forms of translation of these texts into another language. Grahn, American poet, is wellknownfor her political writings and her contributions to the lesbian-feminist movement. Philip, Caribbeanpoet, describes in her poems the experiences of the woman of color during and after colonial and postcolonialtimes. The selected poems are, without a doubt, clear examples of these poets’ ideology and deal withquestions of identity through the interesting mingling of the use of repetition, fragmentation, language playand delay. The option of a type of generative translation that allows conversations with the original texts andthe generation of new images is indeed a valid option to consider.Key Words: generative translation- ideology-language play- delay-fragmentation